Rethinking places of trauma: an interview with Silvia Costa, Government Commissioner for the preservation and re-purposing of the ex-prison complex on the island of Santo Stefano - Bartolini, Flaminia (Ex Novo: Journal of Archaeology, 2021)
Silvia Costa is a journalist and a centre-left politician, she was elected in 2009 at the European Parliament within the SD coalition and from 2020 is the Government Commissioner for the preservation and re-purposing of the ex-prison complex on the island of Santo Stefano. The Ventotene-Santo Stefano project, which has just been dedicated to former EU Parliament President David Sassoli, seeks to preserve material and memorial legacies of two sites of confinement where the very idea of European Union was conceived.